Understanding “Contemporary Hijrah ” phenomenon: A Study of the effect of religiosity on self-esteem - Rochimah - Imawati; Eka Ade Lestari (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2022)
Abstract: A religious phenomenon currently rife in Indonesia is called “hijrah kekinian” (the contemporary hijrah); it is the religious conversion of Muslims living in big cities in Indonesia. Hundreds of Muslims, from various life paths, renew their lifestyle to be more “Islamic”. The author of this article is curious to understand, from a religious, psychological perspective, what psychological consequences are experienced by the perpetrators of the “hijrah kekinian”. Does the increasing religiosity experienced by them influence their self-esteem, which also causes them to be more self-confident and increasingly steadfast and committed to their religious conversion? For this reason, 117 “hijrah kekinian” actors with an age range of 18-40 and above residing in two big administrative cities—South Jakarta and South Tangerang—were sampled and investigated. This study uses quantitative methods, while the sampling technique used is proportional random sampling. The research found that the religiosity variable contributed significantly to the self-esteem variable and had a strong correlation with a correlation coefficient of 0.634, which implies that religious transformation possibly raises self-esteem levels. With the rise, more religious commitment is also increased. Keywords: hijrah kekinian (contemporary hijrah); religiosity; self-esteemAbstrak: Fenomena keagamaan yang marak terjadi di Indonesia saat ini disebut “hijrah kekinian” (hijrah kekinian); itu adalah konversi agama umat Islam yang tinggal di kota-kota besar di Indonesia. Ratusan umat Islam, dari berbagai jalur kehidupan, memperbaharui gaya hidup mereka menjadi lebih “Islami”. tujuan penelitian ini untuk peningkatan religiusitas yang dialami oleh mereka mempengaruhi harga diri mereka, yang juga menyebabkan mereka menjadi lebih percaya diri dan semakin teguh dan berkomitmen pada konversi agama mereka. penelitian ini memahami dari perspektif agama, psikologis, konsekuensi psikologis apa yang dialami oleh para pelaku “hijrah kekinian”. Oleh karena  itu, 117 pelaku “hijrah kekinian” dengan rentang usia 18-40 tahun ke atas yang tinggal di dua kota administratif besar—Jakarta Selatan dan Tangerang Selatan—diambil sampelnya dan diinvestigasi. Penelitian ini menggunakan metode kuantitatif, sedangkan teknik pengambilan sampel yang digunakan adalah proporsional random sampling. Hasil penelitian menemukan bahwa variabel religiositas memberikan kontribusi yang signifikan terhadap variabel harga diri dan memiliki korelasi yang kuat dengan koefisien korelasi sebesar 0,634, yang berarti bahwa transformasi agama mungkin meningkatkan tingkat harga diri. Dengan naiknya, komitmen beragama juga meningkat.Kata kunci: hijrah kekinian; religiusitas; harga diri